TOTAL BAKTERI, PH, DAN KADAR AIR DAGING AYAM BROILER SETELAH DIRENDAM DENGAN EKSTRAK DAUN SENDUDUK (Melastoma malabathricum L.) SELAMA MASA SIMPAN - Melda Afrianti; Bambang Dwiloka; Bhakti Etza Setiani (Universitas Muhammadiyah Semarang, 2013)
The purpose of this study was to determine the number of bacteria, pH, and water content in broiler carcass with soaking senduduk leaf extract at 12 hours of storage at room temperature. The experimental design used was a completely randomized design (CRD) factorial with factor A as the concentration of senduduk leaf extract (a1 = 0%, a2 = 10%, a3 = 15%, and a4 = 20%) and factor B as shelf life (b1 = 6 hours and b2 = 12 hours). The results showed that broiler carcass soaked with senduduk leaf extract that gives real total bacteria effects. However, were not significantly affect the pH and water content. In broiler carsass is 3,21 x 103 total bacterial cfu / g after storage for 12 hours at room temperature. However, this number is still below the limit of microbial contamination (No. SNI. 01-6366-2000).